Morfometrik Ikan Bileh (Rasbora sp.) dari Perairan Ie Sayang Kabupaten Aceh Barat - Zulfadhli, Zulfadhli; Hendri, Afrizal; S, Irhami; Nasution, M. Arif (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Bileh fish (Rasbora sp.) is a fish that lives in freshwater and can be found in the waters of Ie Sayang West Woyla West Aceh District. Excessive exploration has caused the population of bileh fish in nature to decrease and be limited. The first step that needs to be done in aquatic resource management is to identify the type of bileh fish to adopt its cultivation techniques. Fish identification can be done morphologically or molecularly. Morphological identification refers to morphometric studies. This study aims to identify bileh fish species from Ie Sayang waters based on morphometric characteristics. The bileh fish was obtained from community catches in September-November 2023. Morphological identification was done by visualizing and measuring morphometric characters. Data were analyzed descriptively, and the relationship between morphometric characters was analyzed by linear regression. The morphology of bileh fish has a fusiform body shape, terminal mouth type, forked caudal fin, and linea lateralis visible from the operculum to the caudal part. Total length (TL) ranged from 36.94-65.78 mm and standard length (SL) 29.01-52.49 mm. The length-weight correlation of allometric fish was negative. TL characters were closely correlated with SL, HL, DFD, ED, CPD, and VFL.